Memahami Konsep Desain Pembelajaran Serta Evaluasi Penilaian dalam Pembelajaran Pendidikan Agama Islam - Tifani Asnita Putri; Laily Rahma Wati; Gusmaneli Gusmaneli (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The purpose of this paper is to deeply understand the concept of learning design and assessment evaluation in learning Islamic Religious Education. The research method used in this paper is a literature study, which aims to analyze and understand the concept of learning design and assessment evaluation in Islamic Religious Education learning. Literature study is conducted by collecting, reviewing, and analyzing various relevant literature sources, such as books, scientific journals, articles, and other academic documents. The results of this study show that the learning design of Islamic Religious Education aims to create effective learning by integrating Islamic values and modern education needs. The process includes competency analysis, selection of approaches and strategies, and evaluation of learning outcomes. The main principles of this design are the integration of Islamic values, the use of Islamic educational technology, active learning, inclusive, and comprehensive evaluation. PAI learning evaluation measures the achievement of objectives in cognitive, affective and psychomotor aspects, using instruments such as tests and observations. Evaluation results provide a basis for learning improvement and support learner development.